Episodic Autobiographical Memory in Adults With Autism Spectrum Disorder: An Exploration With the Autobiographical Interview - Coutelle, Romain; Goltzene, Marc-André; Canton, Marie; Campiglia-Sabourin, Mélodie; Rabot, Juliette; Bizet, Éric; Schoenberger, Marie; Berna, Fabrice; Danion, Jean-Marie (Frontiers in Psychiatry, 2021)
Introduction: The literature has provided contradictory results regarding the status of episodic memory in ASD. This might be explained by methodological differences across studies. In the present one, the well-recommended Autobiographical Interview was used in which important aspects of episodic memory were assessed namely the number and richness of phenomenological memory details, before and after a retrieval support. Method: Twenty-five well-documented adults with ASD without Intellectual Disability (9 women) and 25 controls participants were included and asked to recall 6 specific autobiographical events. The number and richness of details, were assessed globally and for 5 categories of details (perceptual/sensory, temporal, contextual, emotional, and cognitive), firstly before and then after a specific cueing phase consisting in a series of specific questions to elicit more precise memory details. Results: Cumulatively, from the spontaneous recall to the cueing phase, the number of internal details was lower in ASD individuals compared to controls but this difference was relevant only after the specific cueing procedure and observed only for contextual details. In contrast no relevant group difference was observed during spontaneous recall. The detail richness was not impaired in ASD throughout the Autobiographical Interview procedure. Conclusion: Our results speak against a clear impairment of episodicity of autobiographical memory in ASD individuals. They thus challenge previous ones showing both a reduced specificity and episodicity of autobiographical memory in this population and call for further studies to get better understanding on the status of episodic autobiographical memory in ASD.